Comparative characteristics of biological age and rate of aging of internally displaced and local students - Boiarska, Zoryna; Dotsenko, Olga (ScienceRise: Biological Science, 2019)
Our goal is to study the biological age and the aging rate of students, who have the status of internally displaced persons 2-4 years after evacuation from uncontrolled territories in order to determine the leading factors of aging for further development of preventive measures. Materials and research methods: We surveyed 106 students of Vasyl Stus Donetsk National University. The students’ biological age was determined by the method of Vladimir Voitenko. Results: the biological age of internally displaced male students was found to be 41.3 years on average (passport age 21.8 years), 89.4 % higher than the calendar age. A survey of students of the same chronological age, who reside in the city of Vinnitsa found that their biological age was 37.6 years (passport age - 20.5), which is 83.4 % higher than the calendar age. The biological age of internally displaced female students has increased to 25.8 years (passport age is 20 years), which is 29 % higher than the calendar age. The biological age of local female students is 29.2 years (passport age is 20 years), which is 46 % higher than the calendar age. A study of the aging rate of students found that about half have strongly increased rates of aging. When studying the rate of aging of female students, it was found, that only 12 % had a strongly increased rate of aging. In addition, in internally displaced students (60.6 %), the rate of aging is within normal limits. Conclusions: The biological age and aging rate of male students are strongly increased, with no significant differences between internally displaced and local students. The biological age and the aging rate of female students is progressing not so fast, the internally displaced female students have indicators that are within the normal range for the population